DNA methylation of immune checkpoints in the peripheral blood of breast and colorectal cancer patients. (1st February 2019) - Elashi, Asma A.; Sasidharan Nair, Varun; Taha, Rowaida Z.; Shaath, Hibah; Elkord, Eyad
ABSTRACT: Aberrant expression of immune checkpoints (ICs) in cancer creates an immunosuppressive microenvironment, which supports immune evasion of tumor cells. We have recently reported that epigenetic modifications are critical for ICs expression in the tumor microenvironment (TME) of primary breast cancer (PBC) and colorectal cancer (CRC). Herein, we investigated transcriptomic expression of ICs (PD-1, CTLA-4, LAG-3, TIM-3, TIGIT) and PD-L1 in peripheral blood of PBC and CRC patients, compared to healthy donors (HD). We found that expressions of TIM-3, TIGIT, PD-L1 were significantly upregulated, while LAG-3 expression was downregulated in peripheral blood of PBC and CRC patients. Demethylation enzymes TET2 and TET3 were also upregulated. In addition, promoter DNA methylation status of PD-1 was significantly hypermethylated, while PD-L1 was hypomethylated in PBC and CRC patients. Furthermore, TIGIT was significantly hypomethylated only in CRC patients. Remarkably, promoter methylation status of LAG-3, TIGIT and PD-L1 was in concordance with transcriptomic expression in CRC: the more the hypomethylation, the higher the expression. In comparison, we found that CTLA-4, TIM-3, TIGIT and PD-L1 in PBC, and CTLA-4 in CRC patients were significantly upregulated in peripheral blood, compared with tumor tissues of the same patients. However, demethylation status of all ICs was higher in TT, except for TIGIT in PBC, and CTLA-4 in CRC patients. These data indicate that the underlying mechanisms behind peripheral upregulation of PD-L1 and TIGIT in cancer patients could be due to aberrant promoter methylation profile. Moreover, demethylation inhibitors together with anti-PD-L1/anti-TIGIT could be a more efficient therapeutic strategy in cancer patients.